2011
DOI: 10.1111/j.1524-4725.2011.01953.x
|View full text |Cite
|
Sign up to set email alerts
|

Activated Platelet-Rich Plasma Improves Fat Graft Survival in Nude Mice: A Pilot Study

Abstract: PRP treatment improved the survival and quality of fat grafts. Safer methods of PRP activation and preparation should be further investigated for potential application in humans.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
70
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(73 citation statements)
references
References 37 publications
1
70
1
Order By: Relevance
“…Oh et al mixed human lipoaspirated fat graft and activated PRP (by thrombin and CaCl 2 ) at a ratio of 7:2 and implanted it on the scalps of nude mice. 18 They found higher PRP volume and weight in the control group after 10 weeks. The histology was analyzed, but only with a semiquantitative method with a grading scale.…”
Section: Preclinical Studiesmentioning
confidence: 93%
See 1 more Smart Citation
“…Oh et al mixed human lipoaspirated fat graft and activated PRP (by thrombin and CaCl 2 ) at a ratio of 7:2 and implanted it on the scalps of nude mice. 18 They found higher PRP volume and weight in the control group after 10 weeks. The histology was analyzed, but only with a semiquantitative method with a grading scale.…”
Section: Preclinical Studiesmentioning
confidence: 93%
“…Although some successful clinical results were reported, 16,17 evidence supporting the application of PRP combined with fat grafts in soft tissue augmentation remains limited, as only a few basic research and preclinical studies in small animals have been conducted. 15,[18][19][20][21][22][23] Furthermore, no details on molecular mechanisms are addressed in the literature. In this review article, we discuss the possible molecular mechanisms of PRP in fat graft survival based on a review of the current literature.…”
Section: Introductionmentioning
confidence: 99%
“…Fat graft volume and weight were found to be significantly higher in the PRP group than in the control group. Histologic evaluation showed greater vascularity, fewer cysts and vacuoles, and lesser fibrosis in the PRP group [27].…”
Section: Scars and Dermal Augmentationmentioning
confidence: 99%
“…Because of this, PRP is frequently used today in craniofacial, orthopedic, and neurological surgery [8][9][10][11] . PRP increases the success of grafting when fat grafts are applied in various regions of the body [11][12][13][14] . Moreover, Erkilet et al [15] showed positive effects of PRP when used on its own on the tympanic membrane.…”
Section: Introductionmentioning
confidence: 99%